A DESCRIPTIVE ANALYTIC MODEL OF INTERNET USAGE AND STUDENT PERFORMANCE - Shakiroh Khamis; Azizah Ahmad; Mazida Ahmad (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
The rapid growth of the Internet in this era can be attributed to its increased ease of use, especially among university students. The Internet has become the backbone for students to interact and get information or resources for academic purposes. Students Internet usage data is important and can be used for Universities, Faculties, and Departments. These data can provide useful information if utilized optimally. Therefore, the descriptive study of Internet usage among university students was developed. This research applied descriptive quantitative research where the sample set from 220 respondents. The results indicated that there is a difference between Internet usage in terms of students’ gender, citizen, level of education, current semester and their CGPA. This study also identifies the percentage of users visited websites categories based on 11 categories underline by the university. Researcher successfully identifying a lot of students who are surfing the internet is composed of students who have a high CGPA. This suggests that future research need to work on the impact and implications of internet usage for students based on the category